An efficient isogeometric topology optimization using multilevel mesh, MGCG and local-update strategy. (January 2020) - Wang, Yingjun; Liao, Zhongyuan; Ye, Ming; Zhang, Yu; Li, Weihua; Xia, Zhaohui
Highlights: A high-efficiency isogeometric topology optimization (HITO) is proposed to improve the computational efficiency significantly. The ITO is accelerated by multi-level meshes, MGCG solver and local-update strategy. The sensitivity analysis based on IGA and the NURBS filter technique are given in detail. The proposed HITO can be easily extended to other control-points based ITO problems. Abstract: This paper proposes a new high-efficiency isogeometric topology optimization (HITO), including three part: multilevel mesh, multigrid conjugate gradient method (MGCG) and local-update strategy, which improves the efficiency in three aspects: mesh scale reduction, solving acceleration and design variables reduction. Four benchmark examples are used to evaluate proposed method, and the results show that the proposed HITO successfully reduces 37%–93% computational time compared to the conventional isogeometric topology optimization (CITO) and obtains consistent optimization results, which demonstrates the high-efficiency of the HITO. Furthermore, the efficiency improvement of the HITO will be more significant for the large-scale problems.